Bean consumption increase in an urban population through an educational Campaign. - Rodríguez, Ligia (2004)
An evaluation of the“Educational Campaign to Increase Bean Consumption” wascarried out in the same urban community where the Campaigntook place. Such evaluation started in October, 2001, almostone year after the Campaign was launched in the community.This article deals with one of the aspects studied: beanconsumption in families of mothers who were the target groupof the Campaign. The evaluation was made on a representativesample from a population of middle-class families with schoolchildren from the community, which included 66 families.Results show a consumption increase of 21.4 grams of beansper person per day (g/p/day), as compared to the consumptionfound in the assessment made before the Campaign. This is asignificant increase, placing consumption at the same level asthat of the country’s rural areas, where bean consumption hasremained high.